The Development Of Mathematics Learning Media Based On Mobile Learning Through Smart Apps Creator To Improve Mathematical Problem Solving Skills - Nababan, Ginanty; Sitompul, Pardomuan (JURNAL MANAJEMEN PENDIDIKAN, 2025)
In the contemporary education system, integrating technology is paramount in fostering student's problem-solving abilities. This research focuses on developing learning media that ensures validity, practicality, and effectiveness based on mobile learning through Smart Apps Creator to improve mathematical problem-solving skills. The research follows a Research and Development (RD) approach, employing the ADDIE model for its development. The study involved 30 students in tenth grade from SMA Dharma Pancasila Medan. The research results obtained include the average percentage validation by the media expert 85.17% and the material expert 87%, which are highly valid criteria. The percentage of practicality used with an average rate of teacher response questionnaire is 97.89%, and the student response questionnaire is 84.81%. Learning media developed using Smart Apps Creator (SAC) effectively improves problem-solving skills, as shown by the classical student learning completeness reaching 90% with effective criteria. The increase in problem-solving skills was an increase in the medium category, with an average N-gain score of 0.68. As a result, this study shows that creating learning media based on mobile learning through Smart Apps Creator is an effective educational tool that significantly improves student problem-solving skills.